Pain-A-Way (2020)
The use of needles for the insertion of therapeutic agents into the body or blood sampling is a vital element for the execution of immunizing, diagnostic or therapeutic medical procedures. Since these procedures are administered more frequently during the first nine years of age, the main objective of this project is to improve the experience of pediatric patients during medical procedures that require the insertion of needles, such as vaccinations, injections, canalizations or blood sampling. As such, a novel kit was created for its use by medical and healthcare professionals that reduces the perception of pain during these procedures. In this way, we intend to create a more pleasant environment for both the child and their companions, improve the efficiency of medical personnel and healthcare institutions, and improve adherence to these procedures. Although the kit is intended to be mainly implemented in pediatric procedures, its use can be extrapolated to all ages.